Effect of Lime, Mineral Fertilizer and Manure on Soil Characteristics and Yield of Four Maize Hybrids - Marijana Dugalić; Ljiljana Rakočević-Bošković; Dragana Latković; Vera Rajičić; Dragan Terzić; Ljubomir Životić (Agronomy)
Pseudogley soils in Serbia are characterized by poor chemical and physical properties that limit maize yields. Nevertheless, they are still used on large areas due to their favorable topographic position and lack of better-quality soils. It is common practice to regularly apply mineral fertilizers to these soils, but this does not increase maize yields to an economically sufficient level, although the doses are increased. At the same time, the inappropriate application of mineral fertilizers deteriorates soil chemical properties. Lime is only moderately used in Serbia despite its known benefits, whereas manure is not satisfactorily used. Therefore, a two-factorial experiment was set up as a randomized block design with three replications and conducted near Kraljevo, Serbia, to investigate the effect of mineral fertilizers, manure and lime on maize growth. The experiment included three fertilization regimes: F—application of common fertilizer doses, LF—application of the same fertilizer doses with 3 t·ha−1 of lime, and LMF—application of the same fertilizer doses with lime and 30 t·ha−1 of manure. The response of four maize hybrids to different fertilization practices was investigated. The soil was acid, poor in humus, and contained an increased content of mobile aluminum. There was a significant increase in the 3-year average yield of all hybrids in LMF- and LF-treatments compared with F-treatment, 30.7 and 25.6%, respectively. The increase in yield was accompanied by an improvement in soil chemical properties after three years, i.e., increased soil reaction in LF- and LMF-treatments, increased content of available phosphorus, an increase in base saturation by 61 and 75%, and aluminum immobilization by 2.55 and 4.19 fold, respectively, compared to initial conditions. The hybrid NS 640 demonstrated the highest yield when only mineral fertilizers were used, which indicated its tolerance to the unfavorable physical and chemical soil properties and suggested that it can be recommended for growing on pseudogleys without applying amelioration practices. The hybrids NS 6030 and ZP 606 achieved statistically significantly higher yields than the other hybrids when lime and manure were applied, which indicates that adequate fertilization coupled with soil improvement practices should be used in order to achieve satisfactory yields. The obtained results showed that liming can be considered as a longer-term sustainability practice in maize production in Serbia on pseudogley soils, and that there is an array of maize hybrids which can be grown depending on management strategies applied.